Workforce Bullying: Prevalence and its Impact on Wellbeing of Employees (Global Journal of Management and Business Research, 2015)
Purpose: This paper examines the prevalence of workforce bullying in BPO-ITES services in Punjab region. Direct and indirect effects on physical and emotional wellbeing of employee. Further, the paper investigates the effectiveness of organizational initiatives against bullying and its impact on overall satisfaction of the employees. Method: Data were collected from 130 employees in seven ITES-BPO service organizations in the state of Punjab. The research instrument was a questionnaire in three parts. The first section included the participants' demographic information; the other variables were measured in four categories: psychologically violent behaviours, workload, organizational effects and stress.
Keywords: workplace bullying; satisfaction; organizational support; emotional well being